Small-Signal Stability in Low-Voltage DC-Grids (2018)
This paper presents a general methodology for small signal stability analysis in low voltage de grids considering four type of terminals, namely: constant power, constant voltage, constant current and constant impedance. This methodology is useful for academic purposes but also in practical applications which includes dc-distribution and dc-microgrids. Simulation results demonstrated the proposed small signal model is accurate compared to dynamical simulations. © 2018 IEEE.